Effect of organic loading on anaerobic digestion of cow dung: methane production and kinetic study - Aili Hamzah, Adila Fazliyana; Hamzah, Muhammad Hazwan; Che Man, Hasfalina; Jamali, Nur Syakina; Siajam, Shamsul Izhar; Ismail, Muhammad Heikal (Elsevier, 2023)
Organic loading influences the effectiveness of producing biogas through anaerobic digestion. This study set out to investigate the effect of organic loading on the anaerobic mesophilic digestion of cow dung, the parameters involved in the digestion process and to evaluate the kinetics. Anaerobic digestion of cow dung at different organic loading (gVS/L) of 14 gVS/L, 18gVS/L, 22 gVS/L, 26 gVS/L and 30 gVS/L were investigated. Increasing the organic loading increased the methane yield of the cow dung. The highest cumulative methane yield was observed at 30 gVS/L with 63.42 mL CH4/gVS while the highest biogas yield was reported at 192.53 mL/gVS with the highest methane content of 89%. In addition, the modified Gompertz model equation with an R2 of 0.9980 demonstrated strong consistency and a good fit between predicted and experimental data. The high number of substrates added to the systems when increasing the organic loading increased the λ and slow down the nutrient transport and hydrolysis. This study provides current information on the effects of organic loading on the anaerobic digestion of cow dung in batch mode, including experimental conditions and operational parameters.